Some aspects on the excretion of 17-keto-cortical steroids and godanales in adapting to the height - San Martin F., Mauricio (2015)
Differences were observed reaction in the two species studied. Instead of altitude results in increased excretion of metabolites derived from sexoides, cortical and gonadal steroids, variations are more pronounced in rabbits. These results raise the possibility that nonspecific adaptive mechanisms in which predornina protein catabolism, so fleeting that would go unnoticed in observations that are made within 4 days of the change in altitude and rather indicate that in adapting to the height mechanisms exist predominance of protein anabolism. The association of high and ACTH not mask the excretion of metabolites derived from steroids sexoide type. The association of high serum gonadotropin treatment and intensifies, in the rabbit, increased metabolites latter while a reaction in the guinea pig, similar to what occurs with only the altitude change is observed.